Duodenal Metastases From Renal Cell Carcinoma Presented With Melena: Review and Case Report - Ramesh Omranipour; Habibollah Mahmoudzadeh; Freshteh Ensani; Samira Yadegari; Seyed Rohollah Miri (Iranian Society of Pathology, 2017)
Renal cell carcinoma (RCC) metastasis to duodenum is very rare and only a few case reports are available in the literature. We here reported a patient with solitary duodenal metastasis presented with melena six years after right nephrectomy. The patient underwent upper gastrointestinal endoscopy showing ulcerative mass at the second portion of duodenum and biopsy of this mass was consistent with metastatic RCC. Metastasis work up did not find any other site of malignancy, thus Whipple's operation (Pancreaticoduodenectomy) was performed. In conclusion metastasis from RCC should be considered in mind in patients with history of nephrectomy presenting with gastrointestinal symptoms and a complete evaluation, especially endoscopic examination followed by biopsy, is suggested.